Предмет: Алгебра,
автор: 4epb9k
tg(2arctg(-sqrt3/3) + Пи/3 =
Ответы
Автор ответа:
1
1) tg(2arctg(-√3/3) + π/3) = tg(2*(-π/6) + π/3) = tg 0 = 0
2) Если такое условие:
tg(2arctg((-√3/3) + π/3) = tg(2*((-π/6) + π/3) = tg (2*(π/6)) = tg(π/3) = √3
А вообще, проверьте правильность скобок.
2) Если такое условие:
tg(2arctg((-√3/3) + π/3) = tg(2*((-π/6) + π/3) = tg (2*(π/6)) = tg(π/3) = √3
А вообще, проверьте правильность скобок.
Похожие вопросы
Предмет: Окружающий мир,
автор: VeronaKotik
Предмет: Русский язык,
автор: aidann
Предмет: Русский язык,
автор: VafaMurad
Предмет: Математика,
автор: nurlibekov18pejjwq
Предмет: Русский язык,
автор: vad243